Coping Strategies Used by Parents of Children with Visible Burn sequels - Lagos H., Evelyn; Loubat O., Margarita; Muñoz A., Elizabeth; Vera de la F., Paula (Revista de Psicología, 2004)
This research was aimed at relating the coping strategies developed by parents of children suffering from burn injuries and the levels of anxiety presented by the children themselves. For this purpose, a quantitative methodology and a design of the descriptive correlacional type were used. The sample consisted of 49 children, and their accompanying parents, attending treatment at COANIQUEM. The instruments used were Spielberger’s Inventory of Anxiety State – feature for Children and the Lazarus and Folkman’s Ways of Coping Questionnaire. The results indicate that the strategies coming of selfcontrol, Positive Reinterpretation, Planned Resolution and Acceptance of Responsibility correlate significantly with low levels of anxiety in burned children.